2005
DOI: 10.1164/rccm.200406-716oc
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony–Stimulating Factor and Lung Immunity in Pulmonary Alveolar Proteinosis

Abstract: The anti-granulocyte-macrophage colony-stimulating factor (GM-CSF) autoantibody is inferred to cause idiopathic pulmonary alveolar proteinosis (iPAP): the antibody neutralizes GM-CSF and thereby impairs differentiation of alveolar macrophages. Administration of GM-CSF improves respiratory function of patients with iPAP, as confirmed in this study using aerosolized GM-CSF. To elucidate its mechanism, we characterized bronchoalveolar lavage fluid and alveolar macrophages obtained from three patients with iPAP wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 28 publications
6
79
1
1
Order By: Relevance
“…132, 133 Lin et al found a significant correlation between BALF (but not the serum GM-CSF antibodies) and other severity indicators, and subsequent requirement of therapeutic lung lavage. 134 This could be related to compartmentalization leading to differences in BALF and serum antibody levels.…”
Section: Granulocyte Macrophage Colony Stimulating Factor Autoantibodmentioning
confidence: 99%
“…132, 133 Lin et al found a significant correlation between BALF (but not the serum GM-CSF antibodies) and other severity indicators, and subsequent requirement of therapeutic lung lavage. 134 This could be related to compartmentalization leading to differences in BALF and serum antibody levels.…”
Section: Granulocyte Macrophage Colony Stimulating Factor Autoantibodmentioning
confidence: 99%
“…Continúan siendo motivo de estudio los beneficios del trasplante del pulmón en este tipo de pacientes, razón por la cual su manejo aún lo constituyen las medidas de soporte (17). Así mismo, se requieren estudios adicionales para determinar el beneficio potencial de otras terapias experimentales tales como la plasmaféresis y la inmunoterapia anti -linfocitos B (18). A su vez estos pacientes requieren seguimientos periódicos mínimo cada seis meses, con control radiológico y de LDH cada tres meses en el primer año para descartar recaí-das tempranas.…”
Section: Discussionunclassified
“…These findings suggested that aerosolized GM-CSF might be a suitable alternative to whole lung lavage, and results from a phase-1 pilot study, one clinical trial, and one report of a retrospective case series of subjects who were treated with aerosolized GM-CSF support this notion. [124][125][126] In the larger study performed by Tazawa et al 125 (35 subjects), subjects inhaled high (125 g twice daily) and low (125 g once daily) doses of recombinant human GM-CSF every other week over 2 sequential 12- Fig. 7.…”
Section: Granulocyte-macrophage Colony-stimulating Factormentioning
confidence: 99%